Analysis of Calculation and Reporting of Article 21 Income Tax Based on PP NO 58 of 2023 - Mellafya Cyndya Putry; Puji Rahayu; Imarotus Suaidah (Dinasti International Journal of Education Management And Social Science, 2025)
Quantitative descriptive research will analyze how changes in PER 16/PJ/2016 to PP No. 58 of 2023 affect accounting and reporting of Article 21 Income Tax for workers at Restaurant A, Sidoarjo Branch. Data on the calculation of WPOP Income Tax and the calculation of Income Tax payments based on TER imposed by PMK No. 168 of 2023 with the rate of Article 17 of Law on HPP Number 7 of 2021 are calculated and analyzed using quantitative analysis methods. Interpreting and describing computational data to make inferences from research findings about the effect of TER. All estimates of income and Article 21 Income Tax for WPOP workers at Restaurant A, Sidoarjo Branch, totaling 13 people are secondary data. The average effective rate (TER) in the calculation of Article 21 Income Tax for workers does not increase the tax burden, so taxpayers do not need to worry about tax increases. This is because the current tax calculation utilizes the Article 17 paragraph (1) letter a rate. The use of the Average Effective Rate (TER) for calculating Article 21 Income Tax for January to November is intended to make the calculation of monthly taxes for tax periods other than the previous tax period easier, simpler, and more certain. The calculation results of PPh 21 using the Article 17 rate per month for 13 WPOPs at Restaurant A are IDR 585,088.65. Meanwhile, the calculation results of PPh 21 per month based on TER are IDR 322,061. Meanwhile, the calculation results of PPh Article 21 owed by WPOP employees from Restaurant A based on the Article 17 rate are IDR 770,787.64 for December 2024. Meanwhile, for the calculation results based on TER, PPh Article 21 WPOP owed in December is IDR 2,840,971.